Dogmas of empiricism now and then - Vodešil, Petr (Folia Philosophica, 2005)
The author presents fundamental principles of empiricism established in modern philosophy by Locke and Hume as well as Quine’s criticism of these principles. Quine considered two beliefs as dogmas of empiricism: firstly, there is a clear boundary between synthetic and analytical judgments and secondly, language has atomistic nature i.e. every logical judgment has to be a logical combination of certain observational judgments, in other words it has to be a verifiable observation. Quine proposed new version of empiricism, taking for its basis the so-called holism, which calls into question the possibility of verification or negation of an individual sentence. Quine claimed that only a whole theory or a part of it can be verified.